Eksplorasi Pemahaman Konsep IPAS: Efektivitas PjBL-STEAM berbantuan Media Nusantara 3D Explorer - Siska Dwi Aristianti; Fitriyah Amaliyah; Erik Aditia Ismaya (JANACITTA, 2026)
This research is motivated by the low ability to understand the concept of science and natural sciences of fourth-grade students of SDN 1 Gelang caused by learning that is still dominated by conventional methods and memorization so that students have difficulty connecting the material with real phenomena. This study aims to analyze the effectiveness of the STEAM-based Project Based Learning (PjBL) model assisted by Nusantara 3D Explorer media on improving the ability to understand the concept of science and natural sciences of fourth-grade elementary school students. This study uses a quantitative approach with a pre-experimental method of one group pretest-posttest design. The study was conducted at SDN 1 Gelang, Keling District, Jepara Regency in the even semester of the 2025/2026 academic year with a population and sample of 23 students using saturated sampling techniques. The data collection technique uses essay tests to measure conceptual understanding and documentation. The research instrument was validated through expert judgment by material experts and media experts. Data analysis was carried out using normality tests, paired sample t-tests, and N-Gain tests. The results of the study showed a significant difference in the average value between the pretest and posttest with a significance value of 0.001 < 0.05 so that H₀ was rejected and Hₐ was accepted. The N-Gain test result of 0.63 was in the moderate improvement category with a percentage of 63.35% which showed a fairly effective interpretation. Thus, the application of the STEAM-based Project Based Learning model assisted by Nusantara 3D Explorer media was effective in improving the ability to understand the concept of science and science of elementary school students and supporting the creation of more active, contextual, and meaningful learning.  Abstrak  Penelitian ini dilatarbelakangi oleh rendahnya kemampuan pemahaman konsep IPAS siswa kelas IV SDN 1 Gelang yang disebabkan oleh pembelajaran yang masih didominasi metode ceramah dan hafalan sehingga siswa kesulitan menghubungkan materi dengan fenomena nyata. Penelitian ini bertujuan untuk menganalisis efektivitas model Project Based Learning (PjBL) berbasis STEAM berbantu media Nusantara 3D Explorer terhadap peningkatan kemampuan pemahaman konsep IPAS siswa kelas IV sekolah dasar.  Penelitian ini menggunakan pendekatan kuantitatif dengan metode pra-eksperimen tipe one group pretest-posttest design. Penelitian dilaksanakan di SDN 1 Gelang, Kecamatan Keling, Kabupaten Jepara pada semester genap tahun ajaran 2025/2026 dengan populasi sekaligus sampel sebanyak 23 siswa menggunakan teknik sampling jenuh. Teknik pengumpulan data menggunakan tes uraian untuk mengukur pemahaman konsep serta dokumentasi. Instrumen penelitian divalidasi melalui expert judgement oleh ahli materi dan ahli media. Analisis data dilakukan menggunakan uji normalitas, paired sample t-test, dan uji N-Gain. Hasil penelitian menunjukkan adanya perbedaan rata-rata yang signifikan antara nilai pretest dan posttest dengan nilai signifikansi 0,001 < 0,05 sehingga H₀ ditolak dan Hₐ diterima. Hasil uji N-Gain sebesar 0,63 berada pada kategori peningkatan sedang dengan persentase 63,35% yang menunjukkan tafsiran cukup efektif. Dengan demikian, penerapan model Project Based Learning berbasis STEAM berbantu media Nusantara 3D Explorer efektif dalam meningkatkan kemampuan pemahaman konsep IPAS siswa sekolah dasar serta mendukung terciptanya pembelajaran yang lebih aktif, kontekstual, dan bermakna.